(untitled) (Western Journal of Medical and Biomedical Sciences, 2023)
The health seeking behaviour of a community determines how they use health services. Utilisation of health facilities can be influenced by different attitude, perceptions, determinants and effect of increasing cost of healthcare. The objective of this study was to compare attitude, perception, determinant and effect of increasing cost of healthcare of health seeking behaviour of academic staff in two different tertiary institutions in Edo state, Nigeria. Descriptive cross sectional design and multistage sampling techniques were employed for this study. Total respondents recruited for this study was 400. Questionnaires were used to collect the data. The data was analysed using the Statistical Package for Social Sciences software version 26.0 and the results were presented. Statistics test was deployed to test association between variables and set at p<0.05.Comparison of the respondents’ attitude towards health seeking showed that academic staff of Edo State University Uzairue versus academic staff of Federal Polytechnic Auchi visited health facilities for treatment 76(19%) versus 84(21%) respectively(p=0.038); Regarding perception , academic staff of Edo State University Uzairue versus academic staff of Federal Polytechnic Auchi , that skilled medical management is essential 121(30.3%) versus 100(25%) respectively (p=0.001); that health check ups are necessary 173(43.3%) versus 162(38%) respectively(p=0.007). Determinants showed academic staff of Edo State University Uzairue and academic staff ofFederal Polytechnic Auchi reported the most important determinant when seeking healthcare is proximity 12(3%) versus 10(2.5%) respectively (p=0.000); Effect of increasing cost of healthcare 90(22.5%) versus 133(33.3%) respectively (p=0.000); recommendation for relief of cost of healthcare 20(5.0%) versus 39(9.8%) respectively (p=0.003).Conclusively, there is potential for the betterment of attitude, perception and determinants of health seeking behaviour in both tertiary institutions with government intervention(s) and widespread use of universal health coverage schemes to pay healthcare bills to address effect of increasing cost of healthcare.